Efektivitas Ombudsman Provinsi Kepulauan Riau sebagai Lembaga Pengawas Pelayanan Publik di Batam - Emillia Dwi Setiawati Sianipar (Fakultas Hukum, Universitas Internasional Batam, 2019)
The presence of the Ombudsman of the Republic of Indonesia is expected to be able to oversee the delivery of public services for the realization of an effective and efficient, honest, clean, open state administration and free from corruption, collusion and nepotism. However, has the supervision of the Ombudsman of the Republic of Indonesia in particular in Batam been effective? The purpose of this study is to analyze the problem factors and provide solutions to overcome the problems of the Ombudsman of the Republic of Indonesia Representative of the Riau Islands Province in completing reports and efforts to prevent maladministration in Batam City. By using the Law Effectiveness Theory by Soerjono Soekanto and Empirical Legal Research Methods through observations, interviews and questionnaires as the main data source and literature study as supporting data sources, the research results are obtained that the supervision of the Ombudsman of the Republic of Indonesia Representative of the Riau Islands Province in Batam City has not been effective . Problem factors of the Ombudsman of the Republic of Indonesia Representatives of the Riau Islands Province in overseeing public services in Batam City, namely: lack of human resources, lack of budget, lack of report identification, legal uncertainty, lack of support for public service providers, lack of coordination and cooperation between the Ombudsman and public service providers and lack of public awareness. Based on these problems, the researcher's suggestion as a recommendation is that the duties and functions of the Ombudsman run more effectively in accordance with the mandate of the Law, namely: by revising UUORI and implementing regulations for legal certainty, adding to the budget of the Indonesian Ombudsman Representative of the Riau Islands Province, Improving Quality RI Ombudsman HR Representatives of the Riau Islands Province, held cooperation with public service providers, and actively held socialization to the community.